The Arabidopsis bZIP transcription factor family—an update - Dröge-Laser, Wolfgang; Snoek, Basten L; Snel, Berend; Weiste, Christoph (Current opinion in plant biology, 2018)
•bZIPs are evolutionarily conserved eukaryotic transcription factors.•The Arabidopsis bZIP family consists of 78 members classified into 13 groups.•bZIPs perform a plethora of functions in developmental, environmental and stress signalling.•bZIP activity is controlled by a multitude of post-transcriptional and post-translational mechanisms.•bZIP heterodimerisation within and between groups provides a huge combinatorial potential for gene expression control and signal integration. The basic (region) leucine zippers (bZIPs) are evolutionarily conserved transcription factors in eukaryotic organisms. Here, we have updated the classification of the Arabidopsis thaliana bZIP-family, comprising 78 members, which have been assorted into 13 groups. Arabidopsis bZIPs are involved in a plethora of functions related to plant development, environmental signalling and stress response. Based on the classification, we have highlighted functional and regulatory aspects of selected well-studied bZIPs, which may serve as prototypic examples for the particular groups.